2003
DOI: 10.1016/s1631-0721(03)00147-5
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic behaviour of steels during phase transformations

Abstract: That contribution to transformation plasticity of steels arising from the so-called Greenwood-Johnson mechanism is often described using the model developed by Leblond and coworkers. This model made the assumption of purely plastic behaviour. It is extended here to incorporate viscous effects, which are present during some transformations, especially at high temperatures. The predictions of the original and extended models are compared to experimental results for a material for which the second contribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…In [20], elasto-viscoplastic behaviour of austenite was included. As this does not change the essentials of the model, we drop this here.…”
Section: Description Of the Trip Model Due To Leblond And Co-workersmentioning
confidence: 99%
“…In [20], elasto-viscoplastic behaviour of austenite was included. As this does not change the essentials of the model, we drop this here.…”
Section: Description Of the Trip Model Due To Leblond And Co-workersmentioning
confidence: 99%
“…If the temperature reaches T 0 , w is reset to zero. The parameters F i (T), w 0 i (constant) and n i (T) have been obtained by fitting equation (10) to data found in Ref. 12.…”
Section: Advanced Constitutive Modelmentioning
confidence: 99%
“…In order to address these differences in more detail, Fig. 8a and b display respectively the temperature development and hardening parameter w in equation (10) in points A, B, and C versus time. It is revealed that the material points just outside the HAZ, which exhibit the largest deviations, neither experience a phase transformation (point A experiences a partial phase transformation) nor reach the relaxation temperature T 0 of 900uC above which the hardening parameter w is reset to zero.…”
Section: Advanced Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 These parameters have been measured between 400 and 700uC for bainite and martensite and between 700 and 1100uC for austenite. For example, the left part of Fig.…”
Section: Mechanicsmentioning
confidence: 99%